PENTINGNYA MOTIVASI BELAJAR DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Agrifina, Vivia Febbrilian; Vrisilia, Vinka; Agustina, Lia Nanda; Supriyadi, Supriyadi; Izzatika, Amrina (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
The importance of learning motivation in improving student learning outcomes in elementary schools is the study of this article. One of the important substances in learning activities is motivation. Many previous studies have found that student learning outcomes are influenced by their motivation. This is because motivation determines how much effort needs to be put into learning activities to achieve the designed goals. That is why often students' high learning motivation usually triggers good learning results, while students who lack motivation tend to give up easily when facing difficulties in learning and this can have a bad effect on their learning results. Based on motivation to determine the level of achievement of student learning outcomes, this article aims to examine and provide insight into the importance of learning motivation for students in order to achieve a goal in learning based on literature sources and previous research. This type of research refers to the category of research with a qualitative approach that utilizes the literature review method. By using descriptive qualitative research, researchers are expected to be able to describe, analyze and explain in detail through the sentences discussed. This research is also supported by literature results containing aligned theories from the Google Scholar database. This method is useful in generating better insight into the important role of learning motivation in developing student learning outcomes in elementary schools. In this article, researchers study the definition of motivation, its principles, influencing factors of motivation, the role of motivation, learning outcomes, factors that influence learning outcomes, and the correlation between learning motivation and learning outcomes.